Does National Governance Affect the Capital Structure of Listed Firms during the COVID-19 Pandemic? - Kim Quoc Trung Nguyen (Emerging Science Journal, 2023)
This study estimates the macro-economic factors affecting the listed small and medium enterprises' capital structures in Vietnam from 2010 to 2020. The author conducts the quantitative method (generalized method of moments—GMM) with valid instrument variables to solve the endogeneity in regression models, which refers to the determinants of capital structures. Based on the trade-off theory and the pecking order theory, the author provides evidence of macro-economic factors and firm-specific factors in explanations for the capital choices of the Vietnamese firms, including national governance, inflation, COVID-19, firm age, and asset structure. In particular, this study highlights how national governance and COVID-19 influence the capital structure of small and medium enterprises in Vietnam. Doi: 10.28991/ESJ-2023-SPER-04 Full Text: PDF